Benin : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion and Augmentation of Access; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Sixth Review under Poverty Reduction and Growth Facility (PRGF) for Benin. The macroeconomic outlook is weaker for 2009-10, reflecting the impact of the crisis. Real GDP growth is expected to slow down to about 3-4 percent in 2009-10. The authorities' policy response of allowing automatic fiscal stabilizers to work is appropriate. The implementation of structural reforms needs to be accelerated to enhance the competitiveness of Benin's economy and increase its resilience to exogenous shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet